2016
DOI: 10.1186/s12889-016-3119-5
|View full text |Cite
|
Sign up to set email alerts
|

Economic interventions to improve population health: a scoping study of systematic reviews

Abstract: BackgroundRecognizing the close relationship between poverty and health, national program managers, policy-makers and donors are increasingly including economic interventions as part of their core strategies to improve population health. However, there is often confusion among stakeholders about the definitions and operational differences between distinct types of economic interventions and financial instruments, which can lead to important differences in interpretation and expectations.MethodsWe conducted a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In addition, the excess poultry production in the Full Intervention group at endline allowed mothers a sustainable means of livelihood -something that could be sold to support the purchase of other household needs, including medicines, other types of foods that increased the household dietary diversity, clothing, and school fees for children. This reinforces livelihood support interventions that focus on utility and economic improvement to address health-related issues (35,43).…”
Section: Discussionmentioning
confidence: 65%
“…In addition, the excess poultry production in the Full Intervention group at endline allowed mothers a sustainable means of livelihood -something that could be sold to support the purchase of other household needs, including medicines, other types of foods that increased the household dietary diversity, clothing, and school fees for children. This reinforces livelihood support interventions that focus on utility and economic improvement to address health-related issues (35,43).…”
Section: Discussionmentioning
confidence: 65%
“…The literature has now gone beyond investigating the determinants to identifying potential interventions. Khan et al carried out a rapid scoping review [ 22 ] and found 195 systematic reviews of economic interventions. They found that taxes and subsidies could be used to encourage use of services and healthy patterns of consumption, income transfer programs can support individuals to meet their needs and encourage treatment adherence and that incentives can be used to alter provider and patient behavior.…”
Section: Introductionmentioning
confidence: 99%
“…It may include government expenditure that expands basic incomes through social protection programmes or employment, improves transport and infrastructure or promotes a healthier environment. For example, recent evidence has found that social protection expenditures can improve health outcomes and reduce health inequalities (WHO, 2008; Stuckler et al ., 2009; Ataguba et al ., 2015; Khan et al ., 2016). Further research, focussing on countries with more disaggregated government expenditure data, and particularly social protection data, is needed to explore this further.…”
Section: Discussionmentioning
confidence: 99%